The obesogenic side of Genistein - Xiang, Jia; Mlambo, Ronald; Dube, Progress; Machona, Oleen; Shaw, Ibrahim; Seid, Yimer; He, Yongju; Luo, Min; Hong, Tingting; He, Binsheng; Zhou, Wenhu; Tan, Songwen (Frontiers in Endocrinology, 2023)
Genistein (GN) has been highly recommended for its medicinal properties like anticancer, antidiabetic, antihyperlipidemic, antiviral, and antioxidant activities among others. Recently, scientists realized that Genistein is an endocrine disruptor. It is an obesogen that interferes with the endocrine system causing obesity through many mechanisms like inducing adipocyte differentiation, lipid accumulation, and transformation of some stem cells into adipocytes (bone marrow mesenchymal stem cells for example) in vitro. Animal studies show that GN upregulates genes associated with adipogenesis like CCAAT/enhancer binding protein alpha (Cebpα), CCAAT/enhancer binding protein beta (Cebpβ), and PPARγ. In silico studies reveal a strong binding affinity for estrogen receptors. All these findings were contingent on concentration and tissues. It is beyond dispute that obesity is one of the most frustrating medical conditions under the sun. The pathophysiology of this disease was first attributed to a high-calorie diet and lack of physical activity. However, studies proved that these two factors are not enough to account for obesity in both children and adults. This mini review highlights how Genistein interaction with the peroxisome proliferator-activated receptor gamma protein can cause obesity.